Human autologous rosette-forming cells. V. Study of MHC control in erythrocyte-lymphocyte interaction - Fournier, Catherine; Charreire, Jeannine; Dausset, Jean (Human immunology, 1986)
The role of the major histocompatibility complex (MHC) in human autorosette formation was studied. On a large series of healthy subjects who were typed for HLA antigens, we tested in blind rosette formation with 90 autologous and 295 allogeneic red blood cells (RBC). We found that the mean levels of auto- and allorosettes were similar, being significantly higher in females than in males. However, we failed to find any role for blood group antigens and any involvement of HLA antigens in the interactions between lymphocytes and RBC in rosette formation. Moreover, high or low autorosette levels were not associated with a particular HLA allele. The comparison of individual percentages of auto- and allorosettes indicated that 51% of the subjects displayed identical levels of auto- and allorosettes whereas 29% formed preferentially rosettes with auto- rather than allo-RBC and 20% exhibited lower autorosette than allorosette levels. Among the group of subjects who were better responders for autorosettes than allorosettes, we found an increased frequency of the haplotype A29, B44. Taken together these findings suggest that in contrast to the murine situation, the autorosetting phenomenon in humans is not HLA restricted.